THE IMPORTANCE OF THE UZBEK-FRENCH INTERNATIONAL EXPEDITION IN THE STUDY OF THE STONE AGE MONUMENTS OF THE ELEGANT OASIS. - Amonov Saidazimxon To’raxon o’g’li; Tursunova Marjona Muxtorovna (Journal of new century innovations, 2022)
Annotation: This article focuses on the importance of studying the Stone Age monuments of Zarafshan oasis about how the stone age is divided into stages, tools, new archeological monuments related to the stone age and how the stone age people living in the modern world lead a life.